DOES THE FROG BOIL IN EUROPE? : Frog-in-the-pan momentum and Stoxx Europe 600 - Asunmaa, Antti-Jussi (My University, 2019)
Momentum is one of the most studied and robust anomalies in financial markets. There have been numerous studies that tries to increase its performance by adding other both risk- and behavioral based variables. One of the behavioral based variables is information discreteness by Da et al. (2014), which measures the relations between positive and negative return days. Information discreteness acts as proxy for investors limited information processing capacity. Aim of the thesis is to study wether double sorting a portfolio first by momentum and then by information discreteness generate risk-adjusted returns on European markets. This thesis also extends the existing literature by studying another sample period and different continent. Using the constituents of Stoxx Europe 600 index as test assets and time-period from 11/2005 to 8/2019, test portfolios are formed by double sorting stocks into quantiles first by its J-month cross-sectional momentum and then by the ID measurement. A total number of test portfolios is 25 per formation and holding period. Returns of the test portfolios are then regressed against Fama and French (1993 & 2015) factor models that also includes the momentum factor. Also, average returns, return distributions and firm characteristics in test portfolios are studied. Information discreteness based momentum strategy does not generate risk-adjusted returns. In every tested portfolio, alpha is not significantly different from zero. The momentum factor is mostly the only factor with a significant loading, which indicates that that factor drives the returns of the test portfolios. Mean returns of the double sorted portfolios, both long only and long-short, are mostly higher than their plain momentum benchmark returns.
Keywords: momentum; limited attention; behavioral finance; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance